Assessment of MRI image distortion based on 6 consecutive years of annual QAs and measurements on 14 MRI scanners used for radiation therapy. Issue 1 (16th November 2022) - Lu, Lanchun; Yang, Xiangyu; Raterman, Brian; Jiang, Xia; Meineke, Matthew; Grecula, John; Blakaj, Dukagjin; Palmer, Joshua; Raval, Raju; Thomas, Evan; Hintenlang, David; Gupta, Nilendu
Abstract: Purpose: To determine the magnitude of MRI image distortion based on 6 consecutive years of annual quality assurances/measurements on 14 MRI scanners used for radiation therapy and to provide evidence for the inclusion of additional margin for treatment planning. Methods and materials: We used commercial MRI image phantoms to quantitatively study the MRI image distortion over period of 6 years for up to 14 1.5 and 3 T MRI scanners that could potentially be used to provide MRI images for treatment planning. With the phantom images collected from 2016 to 2022, we investigated the MRI image distortion, the dependence of distortion on the distance from the imaging isocenter, and the possible causes of large distortion discovered. Results: MRI image distortion increases with the distance from the imaging isocenter. For a region of interest (ROI) with a radius of 100 mm centered at the isocenter, the mean magnitude of distortion for all MRI scanners is 0.44 ± 0.18 mm 0.44 ± 0.18 mm, and the maximum distortion varies from 0.52 to 1.31 mm 0.52 to 1.31 mm depending on MRI scanners. For an ROI with a radius of 200 mm centered at the isocenter, the mean magnitude of distortion increases to 0.84 ± 0.45 mm 0.84 ± 0.45 mm, and the range of the maximum distortion increases to 1.92 − 5.03 mm 1.92 - 5.03 mm depending on MRI scanners. The distortion could reach 2 mm at 150 mm from the isocenter. Conclusion: An additional margin to accommodate image distortion should be considered for treatment planning. Imaging with proper patient alignment to the isocenter is vital to reducing image distortion. We recommend performing image distortion checks annually and after major upgrade on MRI scanners.